Understanding Changes in Architectural Form-Function-Meaning Relations: in the Case of Kampong Aquarium, Jakarta, Indonesia. - Ashadi Ashadi; Ratna Dewi Nur'aini; Anisa Anisa; Finta Lissimia; Suriani Ngah Abdul Wahab (International Journal of Built Environment and Scientific Research, 2024)
The history of architectural theory can be seen as a debate between those who place more emphasis on form than function. or vice versa. It is around these themes that the differences between the architects of the late 19th century and the Modernists are best understood. Then came the architects of the postmodern period, in about the last quarter of the 20th century, who added aspects of meaning and considered them important in architecture. This paper aims to understand the form-function-meaning relation in architecture in the case of Kampong Aquarium, Jakarta, Indonesia, with an architectural qualitative descriptive method. The results of the study show that there has been a significant change in the form-function-meaning of Kampong Aquarium, especially since the evictions in 2016. Because the phenomenon of Architectural Change (form-function-meaning relationship) Kampong Aquarium is relatively new, there has not been much research on it. So that this research is expected to open up opportunities for further research with the same theme.